Analysis of Genetic Variability and Heritability in Brinjal (Solanum melongena L.) Genotypes - Tabasum, Saima; Nazir, Gazala; Hussain, Khursheed; Ali, Gowhar; Nazir, Nageena; Mushtaq, Faheema; Hussain, Z.; Arizoo (Journal of advances in biology & biotechnology, 2024)
Analysis on “Study of genetic variability and heritability in brinjal (Solanum melongena L.) genotypes” was carried out at the experimental field of Division of Vegetable Science, FOH, SKUAST, Kashmir Shalimar during kharif season 2021 in Randomised Complete Block Design with three replications. The experimental material comprised of forty genotypes. Analysis of variance revealed that mean sum of squares due to genotypes for all the characters were highly significant, revealing significant variation among all the genotypes for all the traits under study. The phenotypic coefficients of variation were found to be higher than the corresponding genotypic coefficients of variation. The phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) in present experienment were high for the traits; average fruit weight (43.69% and 43.69%), total anthocyanin content (39.10 % and 39.10%), ascorbic acid (31.73 % and 31.73) and dry matter (42.31% and 42.29). Heritability in broad sense was found to be high for all traits under study (greater than 70 per cent). Highest genetic advance as percentage of mean was recorded in average fruit weight (90) followed by dry matter (87.11) and total anthocyanin content (80.55).